An Overview of Disputes Regarding the Right of Structure in Indonesia: Suatu Gambaran Sengketa Terkait Hak Guna Bangunan di Indonesia - Fitra, Said; Purwaningsih, Sri Budi (Rechtsidee, 2022)
Recently, there have been many disputes regarding land rights, namely the Right to Build. The Right to Build is a right that is obtained to use a building on a land that is not one's own for a certain period of time. This study aims to find out the portrait of disputes related to building use rights in Indonesia in 2021. The research method that the author uses is normative juridical using an approach to legislation (Statue Approach) carried out by examining all laws and policies that are in accordance with legal issues being studied. The benefit of this research is to be a reference and input of knowledge for further researchers regarding the Portrait of a dispute over building rights in Indonesia. The analysis of the legal material used is deductive reasoning, what is meant by deductive reasoning analysis here is reasoning based on a mindset that has a general nature to draw conclusions on a specific nature.